1979
DOI: 10.1016/0079-1946(79)90076-4
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical distribution of rare earths and other trace elements in plants and soils

Abstract: The r a r e earthxconcentrations i n vegetables (corn, potatoes, peas and butternut squash) have been found t o be extremely low: g/g-1 0 "~ g/g. The chondritic normalized vegetable REE patterns a r e fractionated, including a negative Eu anomaly, and behave as a smooth function of t h e REE ionic r a d i i. These patterns may be governed by the geochemistry of accessory minerals i n the host s o i l s. The depletion f a c t o r s f o r various elements by vegetables r e l a t i v e t o bulk s o i l s a r e f

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 2 publications
1
13
0
1
Order By: Relevance
“…Direct rhizospheric acidification of the mineral particles (mostly Fe/Mn-oxy(hydroxide) and clay particles) is the suggested physicochemical process by which REE+Y are made soluble and available for uptake by plants (Brioschi et al, 2013). In terms of the correspondence between soils and plant REE+Y signatures, complex relationships between concentrations in these media have been demonstrated (Laul et al 1979;Robinson et al 1958;Tyler and Olsson 2005). This complexity is due to differing REE+Y concentrations within soil horizons and species-dependent absorption capabilities (Lima e Cunha et al, 2014).…”
Section: Ree+y Translocation To Plantsmentioning
confidence: 99%
“…Direct rhizospheric acidification of the mineral particles (mostly Fe/Mn-oxy(hydroxide) and clay particles) is the suggested physicochemical process by which REE+Y are made soluble and available for uptake by plants (Brioschi et al, 2013). In terms of the correspondence between soils and plant REE+Y signatures, complex relationships between concentrations in these media have been demonstrated (Laul et al 1979;Robinson et al 1958;Tyler and Olsson 2005). This complexity is due to differing REE+Y concentrations within soil horizons and species-dependent absorption capabilities (Lima e Cunha et al, 2014).…”
Section: Ree+y Translocation To Plantsmentioning
confidence: 99%
“…Much research on biogeochemical behaviors and the effects of REEs on the agricultural ecosystem has been conducted (Laul et al 1979, Laul & Weimer 1982Xie 1991;Wyttenbach et al 1998;Zhang & Shan 2001). The research can be roughly divided into four periods, which includes the study on efficiency of REE-based fertilizer (Wu et al 1984), practices on the employment of REE-based fertilizer (Zhang et al 1993), geochemical behaviors of REEs in ecosystems (Market & Zhang 1991;Ichihashi et al 1992;Yuan et al 2001), as well as the physiological process of enhanced yield because of REE application (Wang et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported by Macnicol and Beckett (1985) that tolerable HMTEs contents of plants vary from 30 to 40 mg/kg for Co. So and Co content in the studied leaves of R. canina Markert (1996) g Allaway (1968) h Demir and Özcan (2001) i Vance et al (2003) j Wood and Bormann (1975) k Bowen (1979) l Laul et al (1979) m Shacklette (1980) n Reglero et al (2008) o Chapman (1974) p In μg/kg was lower than this value. However, Damascos et al (2008) reported in their study that average Co content in native species of R. canina fruits is about 0.07 mg/kg and Co content in the leaves of R. canina in the present study exceeds that value.…”
Section: Resultsmentioning
confidence: 74%
“…Sc was reported to be 0.005 in vegetables and 0.07 in grass by Laul et al (1979). Sc in R. canina leaves fell above the normal values of vegetables and grass within 0.1 to 0.3 mg/kg.…”
Section: Resultsmentioning
confidence: 88%